Aktivitas Antijamur Ekstrak Daun Ketepeng Cina (Cassia alata L.) - Oktaviany Triana; Fajar Prasetya; Hadi Kuncoro; Laode Rijai (Jurnal Sains dan Kesehatan, 2016)
Research of potential antifungal Candle bush’s leaf extract (Cassia alata L.) have been done. The research done by the method of extraction by maceration using methanol solvent and continued by fraksinasi. Extract get a tes to know potential the antifungal with diffusion method and used a paper disc in different consentration. Analysis of the test is done by measuring the diameter of the zones of fungal growth inhibitory extract. The result of antifungal activity test shows that Candle bush’s leaf has antifungal activity against M. furfur